2018
DOI: 10.3389/fnins.2018.00760
|View full text |Cite
|
Sign up to set email alerts
|

How Is the Neural Response to the Design of Experience Goods Related to Personalized Preference? An Implicit View

Abstract: Understanding the process by which consumers evaluate the designs of experience goods is critical for firms designing and delivering experience products. As the implicit process involved in this evaluation, and given the possible social desirability bias inherent to traditional methods of product design evaluation in certain conditions, neuroscientific methods are preferred to gain insight into the neural basis of consumers’ evaluation of experience good designs. We here used event-related potentials (ERPs) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…The paradigm in the single-reference condition is similar to most previous consumer preference studies ( Telpaz et al, 2015 ; Goto et al, 2017 ; Ma et al, 2018 ; Tyson-Carr et al, 2018 ). In these study paradigms, only one product is presented in each trial, and participants make a value judgment using only their expectations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The paradigm in the single-reference condition is similar to most previous consumer preference studies ( Telpaz et al, 2015 ; Goto et al, 2017 ; Ma et al, 2018 ; Tyson-Carr et al, 2018 ). In these study paradigms, only one product is presented in each trial, and participants make a value judgment using only their expectations.…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed that N200, LPP, and positive slow waves (PSW) could predict consumer preference for a product with an overall accuracy of 71%, although prediction accuracy varied for different components. Ma et al (2018) found that the N200 and LPP were sensitive to the preferences of the consumers, and Tyson-Carr et al (2018) revealed that low-value items elicited a more pronounced N200 than high-value items.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…LPP is a late-stage ERP component, which reaches its peak between 300 and 800 ms after the onset of a stimulus 27 and is also a commonly examined ERP component. It was reported that LPP is sensitive to the cognitive process of emotion regulation, 16 , 28–30 and a larger LPP amplitude indicates stronger emotional arousal. 18 Thus, given the emotional arousal sensitivity of LPP, in the current study, we proposed that LPP represents an emotional regulation process for the product picture in the later evaluation stage.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, several studies have linked EEG frontal asymmetries to consumer choice prediction and purchase intention (Ambler et al, 2004; Vecchiato et al, 2011). Besides, ERP components were associated with categorizing and evaluating stimuli, P300 (Polich, 2007) and N200 (Folstein and Van Petten, 2008) and most recently P200 and LPP (Ma et al, 2018). Furthermore, ERP component N200 and a weaker theta band was associated to purchase intention (Telpaz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%